The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jtcvs.2013.11.056
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between margin distance and local recurrence among patients undergoing wedge resection for small (≤2 cm) non–small cell lung cancer

Abstract: In wedge resection for small non-small cell lung cancer, increasing the margin distance ≤15 mm significantly decreased the local recurrence risk, with no evidence of additional benefit beyond 15 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(105 citation statements)
references
References 25 publications
1
102
1
1
Order By: Relevance
“…Although there is no conclusive definition of the optimal distance (34,35) between a tumor and the nearest section margin, a margin without malignancy is generally considered to be a crucial factor of recurrence and survival. In uniportal VATS, it can be difficult for surgeons to determine how deep their staple applied to obtain free section margins, especially when patients present with deep and non-palpable nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no conclusive definition of the optimal distance (34,35) between a tumor and the nearest section margin, a margin without malignancy is generally considered to be a crucial factor of recurrence and survival. In uniportal VATS, it can be difficult for surgeons to determine how deep their staple applied to obtain free section margins, especially when patients present with deep and non-palpable nodules.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Mohiuddin et al [27] after reviewing 497 non-biased adult patients who had undergone wedge resections for small (less than 2 cm) NSCLC reported that the overall unadjusted 1 and 2 year local recurrence rates were 5.7% and 11.0%, respectively. However, from the adjusted analyses, an increased margin-distance was significantly associated with a lower risk of local recurrence (P = 0.033), and patients with a 10 mm margin-distances had a 45% lower local recurrence risk than those with a 5 mm distance [hazard ratio (HR) 0.55, 95% confidence interval (CI): 0.35-0.86], while beyond 15 mm, no evidence of additional benefit was achieved.…”
Section: [26]mentioning
confidence: 95%
“…[27] However, both Maurizi et al [26] and Mohiuddin et al [27] did not consider surgical margin cytology in their studies.…”
Section: [26]mentioning
confidence: 99%
“…Mohiuddin et al reported that margin distance in wedge resection affects local recurrence (12). Therefore, securing a sufficient surgical margin with wedge resection is very important.…”
Section: Current Issues and Measures In The Thoracoscopic Wedge Resecmentioning
confidence: 99%